Ultrafast and stable planar photodetector based on SnS2 nanosheets/perovskite structure - Leyla Shooshtari (Nature Portfolio, 2021)
Abstract Two-dimensional (2D) transition metal dichalcogenides are promising candidates of photodetectors where they are commonly grown parallel to the substrate due to their 2D characteristics in micrometer scales from exfoliation of bulk crystals or through high temperature chemical vapor deposition (CVD) methods. In this study, semi-hexagonal vertical nanosheets of SnS2 layered have been fabricated on FTO substrate without using Sn source through CVD method at relatively low temperature (500 °C). Due to exceptional band alignment of triple cation lead perovskite (TCLP) with semi-hexagonal SnS2 nanosheets, an improved photodetector has been fabricated. This type of photodetectors fabricated through lithography-free and electrodes metallization free approach with remarkable fast response (20.7 µs/31.4 µs as rising /falling times), showed high photoresponsivity, external quantum efficiency and detectivity of 1.84 AW−1, 513% and 1.69 × 1011, respectively under illumination of incident light with wavelength of 445 nm. The stability of the photodetectors has been studied utilizing a protective PMMA layer on the perovskite layer in 100% humidity. The introduced growth and fabrication process of the planar photodetector, including one/two dimensional interface through the edges/basal planes of layered materials with perovskite film, paves a way for the large scale, cost-effective and high-performance optoelectronic devices.